OsMADS6 plays an essential role in endosperm nutrient accumulation and is subject to epigenetic regulation in rice (Oryza sativa) - Zhang, Jian; Nallamilli, Babi R; Mujahid, Hana; Peng, Zhaohua (The Plant journal : for cell and molecular biology, 2010)
MADS‐box transcription factors are known for their roles in plant growth and development. The regulatory mechanisms of spatial and temporal specific expression of MADS‐box genes and the function of MADS‐box genes in other biological processes are still to be explored. Here, we report that OsMADS6 is highly expressed in flower and endosperm in Oryza sativa (rice). In addition to displaying a homeotic organ identity phenotype in all the four whorls of the flowers, the endosperm development is severely affected in its mutant. At least 32% of the seeds lacked starch filling and aborted. For seeds that have starch filling and develop to maturity, the starch content is reduced by at least 13%. In addition, the seed shape changes from elliptical to roundish, and the protein content increases from 12.1 to 15.0% (P < 0.05). Further investigation shows that ADP‐glucose pyrophosphorylase genes, encoding the rate‐limiting step enzyme in the starch synthesis pathway, are subject to the regulation of OsMADS6. Chromatin immunoprecipitation (ChIP)‐PCR analyses on the chromatin of the OsMADS6 gene find that H3K27 is trimethylated in tissues where OsMADS6 is silenced, and that H3K36 is trimethylated in tissues where OsMADS6 is highly activated. Point mutation analysis reveals that leucine at position 83 is critical to OsMADS6 function.